(3JWhQ fXQjI GdEOGQI (B/s - (3QhK, hdjes ((3GdbGgQI(B: s (3EjJQGc(B, s, 2001)
(3YUQ eGbHd GdKhQI GdRQGYjI(B-(3eQGMd GdKhQI GdRQGYjI(B- (3eGHYO GdKhQI(B- (3deMI Yf eSJbHd fXQjI GdEOGQIs
Keywords: (3GdEHOGY GdEOGQjs; (3GdEOGQIs; (3fXQjI GdEOGQIs